Uproar [videorecording (DVD)] - Whiteman, Sonia; Dennison, Julian, 2002-; Darby, Rhys, 1974-; Driver, Minnie; Rolleston, James (Breaking Glass Pictures, 2024)
In 1981 New Zealand, 17-year-old Josh Waaka navigates rugby-centric St Gilbert's College. Amidst the Springboks' tour and national protests, he embraces acting and his Maori heritage. Josh faces a choice; conform or stand up for family, future, and identity. 'Uproar' is his heartwarming journey against a nation's struggle.